Self-diffusion coefficient of bulk and confined water: a critical review of classical molecular simulation studies. Issue 4 (24th March 2019) - Tsimpanogiannis, Ioannis N.; Moultos, Othonas A.; Franco, Luís F. M.; Spera, Marcelle B. de M.; Erdős, Máté; Economou, Ioannis G.
ABSTRACT: We present a detailed overview of classical molecular simulation studies examining the self-diffusion coefficient of water. The self-diffusion coefficient is directly associated with the calculations of tracer or mutual diffusion coefficient of mixtures and, therefore, is a fundamental transport property, essential for an accurate description of mass transfer processes in biological, geological (i.e. energy or environmentally related), and chemical systems. In the current review we explore two distinct research areas. Namely, we discuss the self-diffusion of water in the bulk phase and under confinement. Different aspects that affect the diffusion process, including the molecular models, the system-size effects, the temperature and pressure conditions and the type of confinement are discussed. Finally, possible directions for future research are outlined.